INFLUENCE OF MACHINING PARAMETERS AND TOOL GEOMETRY ON TOOL WEAR DURING COBALT CHROMIUM-MOLYBDENUM MICRO DRILLING - Mohd Affifudin, Abdul Patar; Mohd Azlan, Suhaimi; Safian, Sharif; Amrifan S., Mohruni; Muhammad Juzaili, Hisam; Mohd Sallehuddin, Shaharum (Penerbit UTM Press, 2024)
Cobalt chromium (CoCr) alloys find extensive use in medical applications due to their unique mechanical properties, such as high strength and low thermal conductivity. However, machining these alloys poses challenges as they are classified as hard-to-cut materials, leading to issues like short tool life, poor surface quality, and low productivity. Rapid tool wear is a significant problem when machining hard alloys, with cutting parameters, drill bit geometry, and types of cutting fluids being the main factors influencing tool wear. In this study, a series of experiments was conducted to investigate the influence of different cutting speeds and tool geometry on tool wear during micro drilling of CoCrMo. A flood cooling system was employed throughout the study, with a constant machining feed rate of 0.1 mm/rev. Three cutting tools with different point angles (118°, 130°, and 140°) and a diameter of 0.2 mm were utilized. The cutting speeds of 50 m/min, 65 m/min, and 80 m/min were varied. A total of 11 runs were performed, with each run consisting of drilling 30 holes. Forces, torques, and tool wear were measured after every subsequent 10 holes drilled. The results indicate that the combination of a 140° point angle and an 80 m/min cutting speed yielded the best performance, exhibiting the lowest force, torque, and tool wear values. The study highlights the importance of selecting appropriate cutting speeds and tool geometry to minimize tool wear and improve machining efficiency when working with CoCr alloys.